Psychometric properties of the CEMA-A questionnaire: motives for lying - Armas-Vargas, Enrique; Marrero, Rosario J.; Hernández-Cabrera, Juan A. (Frontiers in Psychology, 2023)
Previous research on the motives for lying lacks factorial models that allow grouping of motives into specific categories. The objective of this study is to confirm the factorial structure of the questionnaire of motives for lying (CEMA-A). Participants were 1,722 adults residing in the Canary Islands (Spain) who completed the CEMA-A and the Eysenck Personality Questionnaire (EPQ-R). The four-dimensional structure of the questionnaire was confirmed (χ2= 1460.97, df = 325, p = .001; CFI = .94; TLI = .93; NFI = .93; NNFI = 0.93; RMSEA = .05, CI = .051-.057; SRMR= .04). The four factors of the CEMA-A were Intrapersonal Motivation–Emotionality, Interpersonal Motivation–Sociability, Egoism/Hardness Motivation, and Malicious Motivation, with an internal consistency between .79 and .91. Invariance analyses confirmed the equivalence of the instrument for men and women. The CEMA-A factors positively correlated with Neuroticism and Psychoticism, and negatively with Dissimulation. Extraversion was not related to any of the factors, and only displayed a low negative correlation with Intrapersonal Motivation–Emotionality. Analysis of variance showed that men scored higher in Egoism/Hardness and Malicious Motivation. The CEMA-A has proven capable of apprehending the motives for lying and has adequate psychometric criteria for use in various populations.